Mairil and Nyempet as Child Sexual Violence in Pesantren: Contradictions of Traditional Norms, Religion, and Criminal Law Policy in Indonesia - Tohari, Mohamad; Kamalludin, Iqbal; Suseno, Jarot Jati Bagus; Umar, Achmad Jauhari; Pratami, Bunga Desyana (IJCLS (Indonesian Journal of Criminal Law Studies), 2024)
Pesantren, Islamic educational institutions in Indonesia, traditionally provide dormitories for santri, students dedicated to religious studies from childhood through adolescence. However, adolescence often coincides with heightened curiosity about sexuality, leading to behaviors like "Mairil" and "Nyempet." Mairil involves affectionate interactions between individuals of the same gender, which can escalate to physical actions known as Nyempet, distinct from sodomy. This socio-legal study employs a qualitative approach focusing on substantive justice in criminal policy. The research underscores that Mairil and Nyempet constitute forms of sexual violence prevalent in pesantren. Despite inconsistencies with religious norms and criminal law, enforcement remains inadequate. It advocates for a comprehensive approach involving pesantren and competent authorities to tackle these issues. Key recommendations include enhancing victim protection, enforcing existing laws rigorously, and raising societal awareness through education on individual rights and humanitarian principles. In conclusion, addressing Mairil and Nyempet requires concerted efforts from all stakeholders to ensure justice, protect victims, and promote a more inclusive understanding within Indonesian society and its educational institutions.